Building a Caring Village and Stunting Intervention (Disanah Village, Sreseh District, Sampang Regency) - Rozi, Fahrur; Subairi; Abidin, Zainal (Ihsanniat: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is a global health problem that affects the growth and development of children, especially in rural areas. This article discusses initiatives to optimize stunting prevention in Disanah Village, Sreseh District, Sampang Regency, with a focus on improving human resources and establishing a stunting-aware village. Through the Healthy Kitchen Management Socialization and Assistance Program, stunting prevention efforts are carried out by actively involving the community in managing family nutrition and health. This program includes nutrition counseling, as well as assistance in healthy kitchen management to improve eating patterns and hygiene. The expected results are a decrease in stunting rates, increased nutritional awareness among the community, and the formation of villages that care more about children’s health. This article shows the importance of a community-based approach and ongoing training in creating positive changes at the village level to effectively prevent stunting.